Multi-proteomics and interactome dataset of tick-borne encephalitis virus infected host cells - Liyan Sui; Xuerui Guo; Wenfang Wang; Yueshan Xu; Yicheng Zhao; Quan Liu (Scientific Data, 2024)
Abstract Tick-borne encephalitis virus (TBEV) is a significant viral pathogen transmitted by ticks, causing severe neurological complications in humans across Europe and Asia, highlighting the urgent need for an in-depth understanding of molecular functions of viral proteins and their interactions with the host proteome. Multi-omics analysis of how TBEV hijack cellular processes provides information about their replication and pathogenic mechanisms. Here, we focused on the proteome, phosphoproteome, and acetylproteome of Vero cells infected by TBEV, revealing the host perturbations triggered by TBEV infection. Additionally, we performed protein-protein interactome analysis to examine the interactions between TBEV and the host. We have provided technical validation, demonstrating the high quality and correlation of samples across all datasets, and evidence of biological consistency of virus-infected cells at the proteomic, phosphoproteomics and acetylomic levels. This comprehensive multi-omics dataset serves as a valuable resource for studying TBEV pathogenesis and identifying potential drug targets for TBEV therapy.